The Influence of Management Audit, Internal Control, and Motivation on Employee Performance (Case Study at Gading Medika Hospital, Bengkulu City) - Fathul Hilal Perdanakusuma; Any Diah Gustianti; Nina Yulianasari (Sharia Economic and Management Business Journal (SEMBJ), 2025)
The purpose of this research is to determine the influence of management audit scores, internal control, and motivation on employee performance. This research was conducted at Gading Medika Hospital, Bengkulu City. This research uses a quantitative approach with data collection techniques using questionnaires. The data measurement scale is on a Likert scale. Data were analyzed using multiple regression analysis with the help of the SPSS version 24.0 program. Sample selection used the purposive sampling method. The research results show that management audit (X1) has a significant effect on employee performance, internal control (X2) has no significant effect on employee performance, and motivation (X3) has a significant effect on employee performance. First, a trial of the instrument was carried out with validity and reliability tests involving 70 employees of the Gading Medika General Hospital, Bengkulu City, who were involved again during the research. Analysis prerequisite tests included normality tests and multicollinearity tests. The data analysis test used to test the hypothesis in this study used multiple regression analysis.